2021
DOI: 10.1130/ges02334.1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme metamorphism and metamorphic facies series at convergent plate boundaries: Implications for supercontinent dynamics

Abstract: Crustal metamorphism under extreme pressure-temperature conditions produces characteristic ultrahigh-pressure (UHP) and ultrahigh-temperature (UHT) mineral assemblages at convergent plate boundaries. The formation and evolution of these assemblages have important implications, not only for the generation and differentiation of continental crust through the operation of plate tectonics, but also for mountain building along both converging and converged plate boundaries. In principle, extreme metamorphic product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 400 publications
(739 reference statements)
0
11
0
Order By: Relevance
“…Previous studies found that the EMC reached peak metamorphic P–T conditions of 1.5–2.4 GPa and 500–600°C [ 24 , 25 ], which are converted to thermobaric ratios of 250–333°C/GPa. They correspond to low geothermal gradients of 7.5–10°C/km, which belong to Alpine-type eclogite facies metamorphism [ 26 ]. The eclogite facies HP metamorphism took place at 80–65 Ma according to the studies of different slices [ 25 , 27 , 28 ].…”
Section: Geological Background and Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found that the EMC reached peak metamorphic P–T conditions of 1.5–2.4 GPa and 500–600°C [ 24 , 25 ], which are converted to thermobaric ratios of 250–333°C/GPa. They correspond to low geothermal gradients of 7.5–10°C/km, which belong to Alpine-type eclogite facies metamorphism [ 26 ]. The eclogite facies HP metamorphism took place at 80–65 Ma according to the studies of different slices [ 25 , 27 , 28 ].…”
Section: Geological Background and Samplementioning
confidence: 99%
“…A prograde HP metamorphic age of 85.8 ± 1.0 Ma was obtained at P–T conditions of 1.9–2.0 GPa and 540–550°C [ 25 ], which are converted to thermobaric ratios of 275–284°C/GPa. They correspond to low geothermal gradients of 8.3–8.5°C/km, which belong to Alpine-type eclogite facies metamorphism [ 26 ]. For a slice of the Sesia Zone exposed at the locality of Fondo, south of Quincinetto, a pressure cycling at eclogite facies was proposed with two episodes of HP metamorphism at 80–75 and 70–65 Ma, respectively, with a time lag of less than ca.…”
Section: Geological Background and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Yet another setting for post-collisional magmatism is in metamorphic core complexes, which may form on overthickened crust, or over regions such as backarcs experiencing extension from slab rollback (Vanderhaeghe and Teyssier, 1997;Whitney et al, 2004Whitney et al, , 2013Lamont et al, 2020;Soleimani et al, 2021). In most metamorphic core complexes, the magmas form the cores of gneiss domes, typically forming migmatitic to leucogranite sheets derived from remelting of pre-accreted crust with little or no additional contributions from the mantle (Zheng and Chen, 2021;Zheng and Gao, 2021).…”
Section: Late-to Post-collisional Magmatismmentioning
confidence: 99%
“…Hacker et al, 2015; Huang et al, 2013; Rudnick & Gao, 2014). It is generally accepted that partial melting of crustal rocks can effectively differentiate their protolith composition by generation, segregation and migration of felsic magmas from their sources, giving rise to granites in the shallow level and granulites in the deep level (Brown, 2013; Brown & Solari, 1998; Cipar et al, 2020; Clemens, 1990; Sawyer, 1994; Sawyer et al, 2011; Zheng & Chen, 2017, 2021). Although the geodynamic mechanism of intracrustal differentiation can be deciphered by investigating the structure and composition of granites such as autochthonous granites, granitic veins and leucosomes in well‐exposed granulite and migmatite sections (e.g.…”
Section: Introductionmentioning
confidence: 99%